Contributing Factors in Hospital Internal Communication based on Hospital Managers and Healthcare Personnel's Attitudes: A Qualitative Study - Rita Rezaee; Sahar Zare; Fatemeh Niknam; Ali Akbari; Mohammad Shirdeli; Farshad Falahati; Saeed Aghajani (Shiraz University of Medical Sciences, 2022)
Background: A variety of clinical and administrative employees form a complicated communication network which makes various conflicts and contradictions possible in hospitals. This highlights the significant impact of internal communication in directing healthcare centers as one of the manager's duties. Although improving hospital management is key to improvement of the healthcare delivery, few studies have been conducted to address internal communication as one of the main management tasks in hospitals. The current study aimed to determine the contributing factors influencing internal communication based on hospital managers and healthcare personnel's points of view. Methods: A qualitative study utilizing a content analysis approach was performed. A purposive sampling method was recruited and twenty hospital managers and healthcare staff in Shiraz University of Medical Sciences participated in the study. Semi-structured interviews with open-ended questions were conducted. Data were analyzed using thematic analysis by MAXQDA version 10. Results: Eight managers and twelve healthcare staff including eleven male and nine female subjects participated in the study. Three main themes were discerned: namely "personal factors", "technical factors", and "organizational and structural factors". The participants placed the most emphasis on leadership and new technologies as the influential subthemes. Conclusion: Many factors can affect internal communication, some of which depend mostly on managers to be applied effectively in the hospitals and some on healthcare staff. The identified factors help the managers and staff to recognize how their internal communication can be impressed by these factors and how they can create effective internal communications.